2020
DOI: 10.31616/asj.2019.0048
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Dried Platelet-Rich Plasma Induces Osteoblast Proliferation via Platelet-Derived Growth Factor Receptor-Mediated Signal Transduction

Abstract: This study aimed to evaluate the in vitro pharmacological activity of growth factors (GFs) in freeze-dried platelet-rich plasma (FD-PRP) after storage for 4 weeks. Overview of Literature: Freshly prepared PRP is a rich source of many GFs. We reported that FD-PRP stored for 8 weeks accelerated bone union in a rat posterolateral fusion model equally well as fresh-PRP. However, the pharmacological activity of FD-PRP after longterm storage has not been shown in vitro. Methods: Immediately after preparation, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…In this study, all were combined with an artificial bone substitute, hydroxyapatite/collagen [54]. In addition, these authors confirmed the pharmacological activity of FD-PRP after a four-week storage by examining the PDGFR/ERK signal transduction in osteoblasts [55].…”
Section: Musculoskeletal Applicationssupporting
confidence: 63%
“…In this study, all were combined with an artificial bone substitute, hydroxyapatite/collagen [54]. In addition, these authors confirmed the pharmacological activity of FD-PRP after a four-week storage by examining the PDGFR/ERK signal transduction in osteoblasts [55].…”
Section: Musculoskeletal Applicationssupporting
confidence: 63%
“…For instance, Shiga et al reported that FD-PRP maintained baseline levels of growth factor for an entire 8-week duration [ 6 ] and that FD-PRP accelerated bone formation with artificial bone used in a rat posterolateral fusion model [ 13 ]. Kinoshita et al reported that PDGF in FD-PRP is pharmacologically active in vitro after 4 weeks of storage [ 14 ]. It is also reported that FD-PRP significantly enhanced alkaline phosphatase activity and the mRNA expression level of osteogenic genes in vitro, and also that FD-PRP with scaffolds induced significantly greater bone formation compared to the traditional PRP in a rat calvaria defect [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRP is thought to be effective in tissue regeneration because of its concentrated growth factors: the effectiveness of which can vary depending on the platelet concentration [ 14 ]. Marx suggested that a 4- to 9-fold concentration of platelets in the PB, or 100 × 10 4 platelets/mL, is needed in PRP for tissue healing enhancement [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown that the mechanism whereby PRP promotes bone healing may be that platelets are involved in early response to bone injury and initiate the repair response by releasing growth factors, such as platelet derived growth factor (PDGF), insulin-like growth factor (IGF) and transforming growth factor-β (TGF-β) [ 64 , 65 ]. The healing process of stress fractures also involves the above growth factors, which provides a theoretical basis for the application of PRP in stress fractures.…”
Section: Effects Of Prp On Military Drill Injurymentioning
confidence: 99%
“…Currently, it is not possible to apply PRP to war trauma, but the feasibility of PRP treatment of military drill injury in this review provides a possibility for the application of PRP in war trauma in the future. With the development of technology, PRP can be prepared in new formulations, such as PRP freeze-dried powder [ 64 ] and PRP wafer [ 78 ], or other formulations in the future, like PRP-loaded sterile dressing. Improvement of PRP formulation will render transport and long-term storage more convenient, and it is hopeful that PRP can be used as a trauma dressing in battlefield first aid.…”
Section: Application Prospect Of Prp In War Traumamentioning
confidence: 99%